2022
DOI: 10.3390/mi13050803
|View full text |Cite
|
Sign up to set email alerts
|

A General, Label-Free and Homogeneous Electrochemical Strategy for Probing of Protease Activity and Screening of Inhibitor

Abstract: Proteases play a critical role in regulating various physiological processes from protein digestion to wound healing. Monitoring the activity of proteases and screening their inhibitors as potential drug molecules are of great importance for the early diagnosis and treatment of many diseases. In this work, we reported a general, label-free and homogeneous electrochemical method for monitoring protease activity based on the peptide–copper interaction. Cleavage of peptide substrate results in the generation of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Meanwhile, it was found that the Cu 2+ complexes performed with the His1-containing peptides reveal high activity for the catalytic oxidation of OPD to produce fluorescent 2,3-diaminophenazine (OPDox) and maintained excellent selectivity for PSA detection even in the presence of high concentration of interfering proteins [ 88 ]. Based on the difference in the redox potential and current of Cu 2+ before and after being coordinated by the His1- or His3-containing peptide, Feng et al proposed a general, label-free, and homogeneous electrochemical biosensor for the detection of protease activity [ 89 ]. The angiotensin-converting enzyme (ACE) and thrombin were tested as the analyte examples.…”
Section: Electrochemical Biosensorsmentioning
confidence: 99%
“…Meanwhile, it was found that the Cu 2+ complexes performed with the His1-containing peptides reveal high activity for the catalytic oxidation of OPD to produce fluorescent 2,3-diaminophenazine (OPDox) and maintained excellent selectivity for PSA detection even in the presence of high concentration of interfering proteins [ 88 ]. Based on the difference in the redox potential and current of Cu 2+ before and after being coordinated by the His1- or His3-containing peptide, Feng et al proposed a general, label-free, and homogeneous electrochemical biosensor for the detection of protease activity [ 89 ]. The angiotensin-converting enzyme (ACE) and thrombin were tested as the analyte examples.…”
Section: Electrochemical Biosensorsmentioning
confidence: 99%